HUBUNGAN TINGKAT PENGETAHUAN TENTANG VAKSIN COVID-19 TERHADAP MINAT ANAK USIA 12-17 TAHUN DALAM MELAKSANAKAN VAKSINASI COVID-19 DI DESA KUTUH - Neza Dwiyanti; Ni Wayan Sri Rahayuni (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2022)
Background: Vaccines are substances or compounds that function to form immunity against a disease. Prevention of Covid-19 transmission can be done in a simple way, namely using double masks with the right size, vaccinations, frequent hand washing, avoiding crowds, maintaining distance and ensuring good ventilation. Objective: This study aims to determine the relationship between the level of knowledge about the Covid-19 vaccine and the interest of children aged 12-17 years in carrying out the Covid-19 vaccination in Kutuh Village. Methods: This type of research is observational with a cross sectional design. conducted in Kutuh Village. The sample is children aged 12-17 years who have not vaccinated against covid-19 from July to September 2021. The total sample is 49 children who were selected by purposive sampling method. Data were collected using a questionnaire. The data was analyzed with Chi square to determine the relationship between the level of knowledge about the Covid-19 vaccine and the interest of children aged 12-17 years in carrying out the Covid-19 vaccination. Results : The results showed that after the Chi-Squere Test, the knowledge variable got a p value of 0.002 so that the p value <0.05. Based on statistical tests, it can be found that there is a significant relationship between the level of knowledge about the covid-19 vaccine and the interest of children aged 12-17 years in carrying out the covid-19 vaccination in Kutuh Village. Keywords: Knowledge Level, 12-17 Years Old Children, Interests, Covid-19 Vaccination